The ethics of preventive war - Chatterjee, Deen K. (Cambridge University Press, 2013)
Examines the complex moral and legal issues of preventive warfare, using current debates to shed light on enduring questions about justice, human rights and ethics of war and peace. Of interest to scholars in ethics and political philosophy, political theory, international relations, international law, peace studies.